Utilizing Academic–Community Partnerships With Nursing Students to Improve Hand Hygiene in Elementary Students to Reduce Transmission of COVID-19. (November 2021) - Perry, Julie; McClure, Natasha; Palmer, Rebecca; Neal, Jeremy L.
Coronavirus disease 2019 (COVID-19) has raised awareness about the vital role school nurses have in improving the overall health of children. School nurses provide health promotion within schools, yet over 60% of schools have only a part-time nurse or no nurse. Nursing students may be valuable partners for health promotion and academic–community partnerships may be mutually beneficial to schools of nursing and local schools. Using a nursing student team to teach hand hygiene while school health staff were present provided an opportunity for hands-on training to help the staff master curriculum content and ensure competency. This article describes a collaborative partnership initiative that expanded access to health promotion education in schools to increase knowledge about reducing the spread of infectious disease, such as COVID-19, while providing valuable clinical experiences for nursing students.